Anti-adhesion and Anti-biofilm Potential of Organosilane Nanoparticles against Foodborne Pathogens - Gkana, Eleni N.; Doulgeraki, Agapi I.; Chorianopoulos, Nikos G.; Nychas, George-John E. (Frontiers in Microbiology, 2017)
Nowadays, modification of surfaces by nanoparticulate coatings is a simple process that may have applications in reducing the prevalence of bacterial cells both on medical devices and food processing surfaces. To this direction, biofilm biological cycle of Salmonella Typhimurium, Listeria monocytogenes, Escherichia coli O157:H7, Staphylococcus aureus and Yersinia enterocolitica on stainless steel and glass surfaces, with or without nanocoating was monitored. To achieve this, four different commercial nanoparticle compounds (two for each surface) based on organo- functionalized silanes were selected. In total 10 strains of above species (2 for each species) were selected to form biofilms on modified or not, stainless steel or glass surfaces, incubated at 37°C for 72 h. Biofilm population was enumerated by bead vortexing- plate counting method at four time intervals (3, 24, 48, 72 h). Organosilane based products seemed to affect bacterial attachment on the inert surfaces and/ or subsequent biofilm formation, but it was highly dependent on the species and material of surfaces involved. Specifically, reduced bacterial adhesion (at 3 h) of Salmonella and Escherichia coli was observed (P < 0.05) in nanocoating glass surfaces in comparison with the control ones. Moreover, fewer Salmonella and Yersinia biofilm cells were enumerated on stainless steel coupons coated with organosilanes, than on non-coated surfaces at 24 h (P < 0.05). This study gives an insight to the efficacy of organosilanes based coatings against biofilm formation of foodborne pathogens, however further studies are needed to better understand the impact of surface modification and the underlying mechanisms which are involved in this phenomenon.